Optimasi Level of Detail dan Occlusion Culling dalam Game Aaron Lost in the Jungle - Simatupang, Frans Anderson; Amalia Purnamasari, Dwi (JOURNAL OF APPLIED MULTIMEDIA AND NETWORKING, 2024)
This research analyzes the effectiveness of Culling Occlusion optimization techniques andLevel of Detail (LOD) optimization techniques in improving the performance of non-optimized 3D games.optimized. Using quantitative research methods with an experimental approach.experimental approach. Culling Occlusion is a technique that hides objects that are not visible to the player.that are not visible to the player, while LOD is a technique thatLOD is a technique that displays a version of the object with reduced detail based on the distanceThe results show that by using the LOD technique managed to increase the FPS by 107%, while using theOcclusion Culling technique only marginally improved by 19%. This finding indicates that while both techniques are effective in optimizing performance, the LOD technique provides aboth techniques are effective in optimizing performance, the LOD technique provides a more significant improvementmore significant.